Determinants of Employee Loyalty in Port Vehicle Handling Companies - Samodra, Akhmad Reza; Wibowo; Sitinjak, Tony (OGZ Research & Publishing, 2024)
Objective : This study aims to develop a loyalty model for operational staff in vehicle handling terminal companies by analyzing the impact of Employee Engagement, Organizational Citizenship Behavior (OCB), Trust, and Job Satisfaction on employee loyalty in two Vehicle Handling Terminal Companies in DKI Jakarta and Subang, West Java.Methodology : The research uses a quantitative approach with descriptive and inferential statistics. Focus Group Discussions with experts validate the findings, involving a population of 87 operational staff members. Data is analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM).Research results : Descriptive statistics reveal that operational staff's perceptions of employee loyalty are satisfactory but need improvement. Regarding causality, Employee Engagement has a positive and significant impact on employee loyalty. Organizational Citizenship Behavior (OCB) has a negative and significant effect on employee loyalty. Employee organizational trust significantly influences employee loyalty, while job satisfaction has a positive and significant impact on loyalty.The novelty of this research lies in explaining the loyalty model for operational staff in vehicle handling terminal companies through Employee Engagement, OCB, Organizational trust, and job satisfaction, with Employee Engagement being the dominant factor. Job satisfaction is explained by OCB and Organizational trust, but it does not mediate the relationship between Employee Engagement, OCB, Organizational trust, and employee loyalty